The Influence of Company Characteristics and Corporate Social Responsibility Disclosure on Firm Value on Sri Kehati Index Companies 2016-2020 - Amanda Tiara Salsha Putri; Suripto Suripto (Syntax Literate, 2022)
This study intends to examine and collect empirical evidence regarding the influence of Company Characteristics and Corporate Social Responsibility Disclosure on firm value. This study uses a sample of the IDX Sri Kehati company from 2016 to 2020. The sample of this study was determined using a purposive sampling approach, which resulted in 12 companies being the research sample with observations for 5 (five) years, with a total of 60 companies reporting reports. This research is an example of associative quantitative research. The analytical method used is panel data regression. The result of this study are: (1) Company Characteristics as proxied by Managerial Ownership has a negative influence on Firm value, and (2) Company Characteristics as proxied by Board of Commissioners Size has no significant influence on Firm value. (3) Corporate Social Responsibility Disclosure has no significant influence on firm value. (4) Company characteristics as proxied by managerial ownership, company characteristics as proxied by board of directors size, and Corporate Social Responsibility Disclosure all affect firm value simultaneously.